Feasibility of human sciences research Theoretical study (Journal of Human Sciences, 2025)
Scientific research in general represents an effective means of creating culture and knowledge, raising the level of researchers, and providing a clear vision of the future in which various fields of knowledge are moving. Scientific research, with its multiple methods, is one of the necessary things in any field of knowledge, in addition to having many benefits to human society ; It makes a strong contribution to serving society through the role that research plays in its development, especially since it does not come from purely subjective thought, but rather stems from the needs of society itself and its diligent and continuous search for a solution to its problems, and the exploitation and employment of scientific research in its various specializations in its service. Based on this, research in the various fields of human sciences opens horizons of knowledge for researchers, improves their intellectual, cultural and social skills, increases their capabilities in proving scientific facts, the ability to think soundly, develop the style of writing, and attract those interested in reading and learning about these topics, using various scientific approaches, which contribute effectively to serving society, and this in turn is one of the most important factors in the development of human civilization.